Anodal Stimulation of the Left DLPFC Increases IGT Scores and Decreases Delay Discounting Rate in Healthy Males - He, Qinghua; Chen, Mei; Chen, Chuansheng; Xue, Gui; Feng, Tingyong; Bechara, Antoine (Frontiers in Psychology, 2016)
Previous correlational imaging studies have implicated the dorsolateral prefrontal cortex (DLPFC) in decision making. Using High-Definition Transcranial Direct Current Stimulation (HD-tDCS), the present study directly investigated the causal role of the DLPFC in performing the Iowa Gambling Task (IGT) and the Inter-Temporal Choice (ITC) task. Three experiments were conducted: Exp. 1 (N = 41) to study the left DLPFC, Exp. 2 (N = 49) to study the right DLPFC, and Exp. 3 (N = 20, a subset of those in Exp. 1) to switch the experimental and control conditions. All participants were healthy male college students. For Exps. 1 and 2, participants were randomly assigned to either the HD- tDCS or the sham stimulation condition. For Exp. 3, participants were assigned to the condition they were not in during Exp. 1. Results showed that HD-tDCS over the left DLPFC increased IGT score, decreased the recency parameter in IGT, and lowered delay discounting rate (k) in the ITC task. We discussed the potential roles of impulse control and time perception in mediating the effect of tDCS stimulation of left DLPFC on decision making. Our results have clinical implications for the treatment of disorders involving poor decision-making, such as addictions.